Cognitive and Motor Cortical Activity During Cognitively Demanding Stepping Tasks in Older People at Low and High Risk of Falling - Pelicioni, Paulo H. S.; Lord, Stephen R.; Sturnieks, Daina L.; Halmy, Bethany; Menant, Jasmine C. (Frontiers in Medicine, 2021)
Background: Choice stepping reaction time tasks are underpinned by neuropsychological, sensorimotor and balance systems and therefore offer good indices of fall risk and physical and cognitive frailty. However, little is known of the neural mechanisms for impaired stepping and associated fall risk in older people. We investigated cognitive and motor cortical activity during cognitively demanding stepping reaction time tasks using functional near-infrared spectroscopy (fNIRS) in older people at low and high fall risk. Methods: Ninety-five older adults (71.4 (4.9) years, 23 men) were categorised as low or high fall risk (based on 12 month fall history (≥2 falls) and/or Physiological Profile Assessment fall risk score ≥1). Participants performed a choice stepping reaction time test and a more cognitively demanding stroop stepping task on a computerized step mat. Cortical activity in cognitive (dorsolateral prefrontal cortex, DLPFC) and motor (supplementary motor area and premotor cortex) regions were recorded using fNIRS. Stepping performance and cortical activity were contrasted between the groups and between the choice and stroop stepping conditions. Results: Compared with the low fall risk group (n=71), the high fall risk group (n=24) exhibited significantly greater DLPFC activity and increased intra-individual variability in stepping response time during the stroop stepping task. The high fall risk group DLPFC activity was greater during the performance of stroop stepping task in comparison with choice stepping reaction time. Regardless of group, the stroop stepping task elicited increased cortical activity in the supplementary motor area and premotor cortex together with increased mean and intra-individual variability of stepping response times. Conclusions: Older people at high fall risk exhibited increased DLPFC activity and stepping response time variability when completing a cognitively demanding stepping test compared with those at low fall risk and to a simpler choice-stepping reaction time test. This increased hemodynamic response might comprise a compensatory process for postural control deficits and/or reflect a degree of DLPFC neural inefficiency in people with increased fall risk.